Presence of Glutathione-S-transferase enzime in bovine luteal body. (Gaceta de Ciencias Veterinarias, 2018)
The objective of the present investigation was to identify the presence of enzyme Glutathion-S-transferase with direct immunoflorescence technique in mature luteal bodies (LC) and in regression of dairy cattle. For this purpose, 133 CL of Holstein cows, non-pregnant adults, and two or more lactations were sampled from a commercial farm located in the municipality of Jiménez, Lara State, Venezuela, slaughtered in two industrial slaughterhouses, once obtained the ovaries were transferred in a phosphate buffered saline solution at a temperature of 4 to 8 °C to "Dr Haity Moussatche" Research Unit Laboratory of the Veterinary Sciences Dean of UCLA (DVS-UCLA ) To be assayed, 5 μm slices were subsequently taken where the presence of GST enzyme was determined in each sample and incubated with diluted GST antibody. Descriptive statistics were applied for results analysis. It was observed that in the mature LC, 71.25% had a high content of fluorescent granules (presence of the enzyme) while the remaining 28.75% presented moderate content. On the other hand the LC in regression showed little amount of fluorescent green granules indicating little expression of the enzyme.